The Thirteenth tale - Setterfield, Diane (New York : Atria Books, 2006)
Aging reclusive author Vida Winter, having given out multiple versions of her life story over the years, decides t6o finally set the record straight and engages Margaret Lea, a London bookseller's daughter, to write her biography, drawing the young woman into a tale of a governess, a ghost, a willful woman, feral twins, and a ghotic mansion.
New York Times Bestseller.
Keywords: Recluses as authors -- Fiction; Female friendship -- Fiction; hermits -- Fiction; Women authors -- Fiction